2016
DOI: 10.3201/eid2205.151449
|View full text |Cite
|
Sign up to set email alerts
|

Severe Sepsis and Septic Shock Associated with Chikungunya Virus Infection, Guadeloupe, 2014

Abstract: During a 2014 outbreak, 450 patients with confirmed chikungunya virus infection were admitted to the University Hospital of Pointe-à-Pitre, Guadeloupe. Of these, 110 were nonpregnant adults; 42 had severe disease, and of those, 25 had severe sepsis or septic shock and 12 died. Severe sepsis may be a rare complication of chikungunya virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 13 publications
(14 reference statements)
8
60
0
Order By: Relevance
“…Cardiovascular and neurological involvement were 34% each. This result is similar with another study 22 but differ from other studies where cardiovascular (54%) followed by neurological (37%) involvement 20 or neurological involvement was more frequent. 27 Mortality was 10% in one study where cardiac complications were common 20 and another study showed mortality is 48% in patients admitted in intensive care unit.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Cardiovascular and neurological involvement were 34% each. This result is similar with another study 22 but differ from other studies where cardiovascular (54%) followed by neurological (37%) involvement 20 or neurological involvement was more frequent. 27 Mortality was 10% in one study where cardiac complications were common 20 and another study showed mortality is 48% in patients admitted in intensive care unit.…”
Section: Discussionsupporting
confidence: 90%
“…[22][23][24] Though the guidelines say that diarrhea and vomiting are more common in children but this study revealed that a good number of adult patients had these symptoms as well which we can find in other study also. 25,26 In this study lymphopenia was more frequent that is about 91% and thrombocytopenia was less and that is 43%.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Complications occur in patients of extreme ages -> 65, children, pregnancy, co-morbiditydiabetes mellitus, hypertension, ischemic heart disease and other co-infection. 15,16 In the subacute phase the predominant features is arthritis/arthralgia and fatigue. 17 In 10-15% patients the joint symptoms progress beyond 3 months among whom 50 % patients evolve into rheumatoid arthritis or seronegative spondyloarthitides or non-specific viral arthritis.…”
Section: Chikungunya Fever Epidemiologymentioning
confidence: 99%